Migracijos šeimų „įprobleminimas“: šeimos ir migracijos reprezentacijos oficialiuose Lietuvos politikos dokumentuose - Juozeliūnienė, Irena; Bielevičiūtė, Indrė (Vilnius University Open Series, 2020)
This chapter set up to examine the language of ‘family’ in key policy documents regulating family life in Lithuania. Drawing on theoretical ideas of Ribbens McCarthy the authors look into the ways of framing of family life, identify scripts of ‘normal’ family, and analyse how these, in turn, sought to portray migrant families as ‘troubling’. The research presented here was carried out in January-May 2018 and formed a sub-study of the project ‘Global Migration and Lithuanian Family: Family practices, circulation of care and return strategies’ (2017–2019) funded by the Lithuanian Research Council. Analysis of the strategic policy documents regulating family life in Lithuania in the period from 1995 to 2018 has revealed that the imagined orders of family life evolve over time, which explains the changes in the language used to describe family lives. The authors have identified the ways of portraying Lithuanian ‘family’ as ‘normal’, ‘harmonious’, and ‘sovereign’, and examined how legislators ‘troubled’ migrant families or – in a long run – depicted them as ‘sovereign, but silenced’ and as ‘important, but mysterious’.